Sexualidade: cosmo da vida expresso pelo desenho - Lima, Leidson da Silva (2014)
Design is a polysemic word indicating, among other things, description, project, graphical representation, sketching, recording, drawing. Its use by humanity dates from prehistory. In fact, it is an area of human knowledge that has its own language and, although it does not replace words, does not require them to express a message. Hallawell (2004) defines the design as the interpretation of any reality - emotional, visual, mental - expressed graphically. On the other hand, Gomes (1996) proposes a distinction between drawing as graphical representation , called Sketching by him and drawing that indicates planning , mental intention, which the author calls design. At Renaissance, Mathematics, Geometry and other sciences resources associated with design allowed unique masterpieces productions, which pictures - made on flat surfaces - have three-dimensionality and light and shadow play. In this technique, Leonardo da Vinci (1452-1519) figured as greater name because the tones of light and dark present in drawings and paintings by this artist surpassed those found in his time - a time where it was aimed, as never before, represent the real through art. In this conflicted period - Renaissance - Leonardo composed “Coition of a Hemisected Man and Woman”, the drawing of a sexual relation anatomy. And, as all artists when print information in their Works are not always aware of their creative act, from the question "What elements or componentes of sexuality are represented in Coition of a Hemisected Man and Woman by Leonardo da Vinci? " we conducted an iconographic study aiming to reveal the elements of sexuality present in the mentioned masterpiece, verifying how it connotes or denotes these elements. To Renaissance culture - ruled by the Church thoughts, however, getting rid of it – it would be a sacrilege to represent the interior of human bodies during full intercourse. However, by investigating this "sacrilege" committed by Da Vinci, we could find valuable information nowadays. We have gone through a two-way road to reach our goals, which, regarding to the specific ones were to analyze the drawing aforementioned, relating it to three multifaces of Drawing (subject area): art, design, and graph (meaning graphic representation); identify elements / components of sexuality present in the masterpiece; relate design, health and sexuality from the image, that is, to bring them afloat through designed graphic content that makes up the work and highlight the importance of drawing and image which has elements of health, as the case of sexuality. On the way, we looked for the drawing of "Intercourse" in books and specialized websites; after finding it, we detailed the whole masterpiece in a moment called pre-iconographic description. We checked Leonardo’s artistic mottos associated with his knowledge of human health. And we allowed the drawing image to be the foreground, providing us to unveil its components. Thus, Drawing through its unique language exposed in "Coition" elements of sexuality sublimated in the lines and traces that compose it, referencing the social equilibrium through sexuality, drawn by the art of drawing, in this case, to help people produce health on respect of life, without neglecting the spirituality of this being so bio-psycho-socio-cultural that is the human being.